Occurrence of dolichocolon without megacolon in chronic Chagas disease patients - Castro,Cleudson (2012)
INTRODUCTION: Since 1970, lengthening of the rectosigmoid has been suspected to be a solitary manifestation of Chagas colopathy. METHODS: To test this hypothesis, opaque enema was administered on 210 seropositive and 63 seronegative patients, and radiographs in the anteroposterior and posteroanterior positions were examined blind to the serological and clinical findings. The distal colon was measured using a flexible ruler along the central axis of the image from the anus to the iliac crest. RESULTS: Dolichocolon was diagnosed in 31 (14.8%) seropositive and 3 (4.8%) seronegative patients. The mean length was 57.2 (±12.2)cm in seropositive patients and 52.1 (±8.8)cm in the seronegative patients (p = 0.000), that is, the distal colon in Chagas patients was, on average, 5.1cm longer. Seropositive female patients presented a mean length of 58.8 (±12.3)cm, and seronegative female patients presented 53.2 (±9.1)cm (p = 0.002). Seropositive male patients had a mean length of 55 (±11.6)cm, and seronegative male patients had 49.9 (±7.8)cm (p = 0.02). Among 191 patients without megacolon and suspected megacolon, the mean length was 56.3 (±11.6)cm in seropositive individuals and 52 (±8.8)cm in seronegative patients (p = 0.003). Among individuals with distal colon >70cm, there were 31 Chagas patients with mean length of 77.9 (±7.1)cm and three seronegative with 71.3 (±1.1)cm (p = 0.000). Among 179 with distal colon <70cm, seropositive individuals had a mean length of 53.6 (±8.8)cm, and seronegative patients had 51.2 (±7.8)cm (p = 0.059). Serological positive women had longer distal colon than men (p = 0.02), whereas the mean length were the same among seronegative individuals (p = 0.16). CONCLUSIONS: In endemic areas of Brazil Central, solitary dolichocolon is a radiological Chagas disease signal.